Serial Rectifier Antenna (Rectenna) Circular Microstrip Patch 2.4 GHz for RF Energy Harvesting - Asyifa, Salwa; Pharmayeni, Pharmayeni (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
The rapid development of Radio Frequency (RF) usage at this time causes the abundance and waste of radio frequency (RF) electromagnetic wave energy sources in the air. This RF energy source can be used as an environmentally friendly alternative by harvesting energy using the rectenna system . The rectifier antenna (rectenna) system is designed using the serial rectenna system , this system is used to improve the performance of the rectenna in converting electromagnetic waves into a direct voltage (DC) source. To design a serial rectenna system, use 3 antennas and 3 series of rectifiers . The antenna used in the serial rectenna system is a 2.4 GHz circular microstrip patch antenna for WiFi signal reception. Meanwhile, the rectifier circuit uses a 6-stage voltage doubler using a Schottky 2860 diode and a 1nF smd capacitor. From testing and measuring the serial rectenna system , the circular patch microstrip antenna is able to capture and rectify the voltage to DC. Antenna system has return loss values of -26.29 dB, -21.75 dB, and -28.57dB, VSWR 1.11, 1.16, and 1.07, impedances 51.1, 55.56, and 50.22, bandwidth 60 MHz, 60 MHz and 50 MHz with resonant frequency 2.42 GHz, 2.36 GHz and 2.48 GHz. So that the voltage generated by a single rectenna system is 51.3 mV at a distance of 25 cm. Meanwhile, the rectenna serial system can convert direct voltage of 151.3 mV at a distance of 25 cm from the source of the Access Point transmitter.